Mediastinal lymphoma appeared with cardiac compression in children - Rahman, A.; Kazez, A.; Cekirdekci, A.; Akarsu, S. (My University, 1999)
Two mediastinal lymphoma cases appeared with symptoms of cardiac compression and required emergent operation are presented. Computerized tomography and echocardiography are the best evaluation methods in such cases. The diagnosis, treatment and complications of these cases were discussed.
Cocuklarda kalp basisi ile ortaya cikan mediastinal
Keywords: Cardiac compression; Lymphoma; Mediastinum